PENGARUH PEMBERIAN EKSTRAK BUAH ASAM JAWA (TAMARINDUS INDICA) TERHADAP PENURUNAN KONTRAKSI OTOT POLOS UTERUS TERPISAH MARMUT BETINA (CAVIA PORCELLUS) - Mochamad Ma’roef; Arifatul Jannah2 (Universitas Muhammadiyah Malang, 2015)
Ma’roef, Arifatul. The Influence of Tamarind (Tamarindus indica) Fruit Extract On Reducing Isolated Uterine Smooth Muscle Contraction of Female Guinea Pig (Cavia porcellus) Background : Tamarind (Tamarindus indica) is medicinal plant that is easy to get and has many adventages. Flavonoid, tannin, and some minerals in this plant have been supposed to be able to inhibit uterine contraction that could reduce menstrual cramps and decrease preterm delivery. Objective : To know the influence of tamarind fruit extract on reducing isolated uterine smooth muscle contraction of female guinea pig. Methods : True experimental with post test only control group design. Non-pregnant female guinea pig uterine strips in De Jalon solutions were contracted by 0,03 IU oxytocin and 3 doses of extract were added to the preparation, namely 2 mg/ml (P1), 4 mg/ml (P2), and 6 mg/ml (P3). Those groups were compared to positive control(only oxytocin induced) and negative control (without intervention). The contractions were recorded for 20 minutes and the result was shown in Labscribe2 software. Result : The result of ANOVA showed a significant difference between control group and treatment (p=0,00).The correlation test result showed that the higher dose of tamarind extract, the less contractions will be. Linear regression result showed a strong influence of tamarind extract on reducing uterine contraction, namely 84,7% with 4 mg/ml as effective dose. Conclusion : Tamarind extract has influence on reducing the isolated uterine smooth muscle contraction of female guinea pig.Key word : tamarind, uterine contraction, guinea pig